Strategies for Enhancing Job Satisfaction: The Influence of Rewards, Work-Life Balance & Coworker Support - Nazarwin Nazarwin; Riki Wanda Putra; Bambang Hermanto; Syafni Yelvi Siska (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study aims to examine the effects of rewards, work–life balance, and coworker support on employee job satisfaction. Employing a quantitative design with independent samples t tests, the research population comprised all employees of Politeknik Pelayaran Sumatera Barat in 2025 (150 persons), with a purposive sampling technique based on percentage to select respondents. So, the pilot sample is 37 persons, and the research sample is 113 persons. A structured questionnaire was used to measure the variables of recognition, work–life balance, coworker support, and job satisfaction, and data were analyzed using SPSS. The findings reveal that rewards, work–life balance, and coworker support significantly influence job satisfaction (t-calculated > t-critical; 21.849, 14.508, 21.991 > 1.66). Rewards also impact work–life balance, which in turn affects coworker support, although they do not directly influence it. Implications of this research suggest that implementing a structured reward system can be an effective strategy to enhance job satisfaction in vocational education settings. Future studies are advised to employ mixed methods designs and broaden the sample to multiple institutions to verify and generalize these results. It is recommended that the management of Politeknik Pelayaran Sumatera Barat develop and implement integrated reward programs and flexible work policies to optimize employee well-being and productivity.